Computational Approaches in the Transfer of Aesthetic Values from Paintings to Photographs : Beyond Red, Green and Blue /: Beyond Red, Green and Blue. (2017) - Zhang, Xiaoyan; Constable, Martin; Chan, Kap Luk; Yu, Jinze; Junyan, Wang
No abstract available